Systemic Role for Vitamin D in the Treatment of Psoriasis and Metabolic Syndrome. (5th June 2011) - Fu, Lisa Wenyang; Vender, Ronald
Abstract : The novel discovery of the systemic role of vitamin D in the modulation of the immune system especially the Type 1 helper T cell (Th1) pathway reveals its potential for treating Th1 inflammatory diseases. Psoriasis has been recently established to be a systemic disease centered on inflammation and involvement of cytokines of the Th1 pathway. There is an increased prevalence of metabolic syndrome in patients with psoriasis. Metabolic syndrome also involves a proinflammatory state. This paper proposes the idea of the potential use of oral vitamin D to treat psoriasis and metabolic syndrome concurrently. We propose there is merit in more clinical trials investigating the use of vitamin D to treat both psoriasis and metabolic syndrome through its anti-inflammatory effects. On application to psoriasis management and prognosis, the goal is to decrease the risk for cardiovascular disease and decrease disease morbidity and mortality.